Desmin expression in rhabdomyosarcoma: influence of the desmin clone and immunohistochemical method. Issue 6 (June 1995) - Pollock, L; Rampling, D; Greenwald, S E; Malone, M
Abstract : AIM–To determine which, if any, of five commercially available desmin clones is most reliable at labelling desmin filaments and whether the enhanced polymer one step (EPOS) method of labelling is of any advantage in the routine diagnostic laboratory. METHODS–Thirty four rhabdomyosarcomas from the files at The Hospital for Sick Children, Great Ormond Street, London, were studied. Four different desmin clones, DE-R-11, D33, DE-U-10, and PDE, were applied to each using the conventional extravidin biotin peroxidase method. The D33 clone was also applied using the EPOS method. RESULTS–The EPOS method incorporating D33 persistently scored more cells as desmin positive and was positive in four cases which were negative on staining with the other clones. CONCLUSIONS–The D33 desmin clone used with the EPOS method is more reliable for identifying desmin filaments in tumours than other desmin antibodies tested. Different desmin clones using a routine technique label different rhabdomyosarcoma cells and therefore it is justifiable to use more than one clone.